A kingdom besieged - Feist, Raymond E. (Feist, Raymond E. Chaoswar saga, 2012)
Midkemia's most powerful sorcerer Pug faces a major magical cataclysm that forces him to question everything he's ever held as true and dear ... including the loyalty of his beloved son Magnus.